Perceptions and Practices of Sanitary Workers toward Hepatitis B Virus Infection and Vaccination in Tertiary Care Hospitals of Rawalpindi: A Cross Sectional Analytical Study - Tariq, Naseer Alam; Saeed Awan, Bushra Ameer; Saleem, Samia; Atif, Muhammad; Sahiba, Fatima; Musa, Muhammad; Khan, Mohammad Affaq (Pakistan Armed Forces Medical Journal, 2024)
Objective: The purpose of this study is to evaluate the sanitary staff at selected tertiary care hospitals of Rawalpindi. Study Design: Cross-sectional analytical study. Place and Duration of Study: study was conducted from Nov 2021 to May 2022. In four Tertiary Care Hospitals in Rawalpindi Pakistan. Methodology: The sample size of 200 was calculated as per the reference study. Convenience sampling technique was used.Hospital cleaners over the age of 18 who worked daily in all clinical units and were involved in cleaning, waste collection and disposal. Results: In this study majority of the participants were males 178(89%) and majority 75(38%) were of age group 35-44 years and 45-54 years 69(35%). More than two third 156(78%) were married. Almost equal proportion of participants had middle 83(42%) and primary 77(39%) education There was significant association of gender with knowledge of Hepatitis-B (pvalue=0.004), knowledge of cure (p-value=0.001) and symptoms (p-value=00.02), transmission through blood transfusion (pvalue=0.027). There was also significant association between age group and provision of HBV vaccination to the staff (pvalue=0.009), knowledge of availability of HBV vaccination at hospital (p-value=0.001), screening for HBV (p-value=0.025),handling of sharps carefully (p-value=0.000), vaccination status for HBV (p-value=0.010), wearing gloves during work (pvalue=0.017). Conclusion: the study offers helpful information into potential idiosyncrasies of sanitary workers and hospital cleaners that may serve as the foundation for future, more extensive studies.